Implementation and Analysis of Sentimental Analysis on Facial Expression Using HAAR Cascade Methods - Anand, Dr. Darpan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The sentimental analysis is phenomenon of exploring, analyzing and organizing human feelings. It is a process of extracting feelings of human faro pictures. It involves the separation of image into various characters such as face, background, etc. It uses lips and eye shape for extracting human feelings. It uses numerous of applications such as Pycharm Numpy ,Open CV, Python,etc. Its main objective is to find out the moods of human such as happy , sad ,etc. This report generates the emotional state of human being as well as different emotion of human in different situation.